Indigenous healers' views regarding the causes and treatment of chronic diseases : the case of Ga-Dikgale - Mojalefa, Heirness Mologadi (My University, 2014)
A number of studies have revealed that chronic diseases are common in all communities. This study explored the views of indigenous healers regarding the causes and treatment of chronic diseases in Ga-Dikgale community. A qualitative approach was followed and participants were selected through snowball sampling. Seven participants (2 males and 5 females) who are indigenous healers were recruited for the study. Data was collected using in-depth semi-structured one-to-one interviews and analysed using content analysis. The results of the study are presented in terms of the following themes: a). Participants’ views regarding the types of chronic diseases: despite the divergent views held by indigenous healers regarding chronic diseases, they all perceive these debilitating conditions as incurable. b). Participants’ own explanations of the causes of chronic diseases: it appeared the causes of chronic diseases were attributed to both cultural beliefs and modern medical science. c). Participants’ experiences and subjective notions on the treatment methods for chronic diseases: it was found that Western medicine is considered the most viable option to treat chronic diseases instead of indigenous medicine. d). Participants’ descriptions of the most common diseases that they treat: indigenous healers treat non-chronic conditions instead of chronic diseases. e). Participants’ own perceptions of their roles in the community: it appeared indigenous healers felt they received support from their community as they were consulted mostly for non-chronic conditions; and f). Participants’ recommendations on how people with chronic diseases should be managed: indigenous healers recommend that people should seek medical intervention for treatment of chronic diseases. The study further revealed that indigenous healers in this community are not always the first line of treatment for chronic conditions. Instead, it was found that indigenous healers tend to advice patients with chronic diseases to seek medical intervention rather than traditional healing. The study is concluded by recommending further investigation on chronic diseases, including the possibilities of integrating indigenous healing and Western-oriented health care systems.
Thesis (M.A. (Clinical Psychology)) -- UNiversity of Limpopo, 2014
Keywords: Indigenous healers; Chronic diseases; 616.044; Chronic diseases -- Psychological aspects; Chronic diseases -- Treatment; Healers -- South Africa -- Limpopo